Antagonistic interactions between predator and prey: mobbing of jaguars (Panthera onca) by white-lipped peccaries (Tayassu pecari) - Lilian E. Rampim; Leonardo R. Sartorello; Carlos E. Fragoso; Mario Haberfeld; Allison L. Devlin (acta ethologica, 2020)
Ambush predators rely on stealth to successfully secure prey. Mobbing is a rarely observed anti-predation strategy used by group-living prey species whereby several individuals distract or harass a predator until it either ends the pursuit or leaves the area. Herein, we present three unique cases of white-lipped peccaries ( Tayassu pecari ) mobbing jaguars ( Panthera onca ) in the wild. White-lipped peccaries and jaguars co-occur within the study area, a large-scale ecotourism and working cattle ranch in the Brazilian Pantanal. Two cases of mobbing were recorded by video camera trap during routine surveys, and a third case was directly observed by one of the authors during telemetry triangulation of a GPS-collared individual jaguar. Our observations provide direct empirical evidence of antagonistic behavioral interactions between jaguars and white-lipped peccaries that have previously been limited to anecdotes within academic literature. We discuss the implications of this behavioral interaction for the proximate and ultimate fitness of both predator and prey.